College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 6 - Section 6.1 - Composite Functions - 6.1 Assess Your Understanding - Page 410: 72


See below.

Work Step by Step

We know that if a function is odd, then $f(-x)=-f(x).$ So here $f(x)=-f(x)$ and $g(x)=-g(x)$. Then $f(g(x))=f(-g(x))=-f(g(x))$, thus $f(g(x))$ is also odd, thus we proved what we had to.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.